Indonesian Grammar in Context Volume 2 : Asyik Berbahasa Indonesia - Rafferty, Ellen; Argazali-Thomas, Shintia; Burns, Molly (Book collections on Project MUSE., 2014)
Indonesian Grammar in Context provides beginning, intermediate, and advanced learners with an introduction to the basic grammatical structures of Indonesian in three richly illustrated volumes. Although numerous varieties of Indonesian exist throughout the archipelago, the authors use a relaxed, conversational style of Indonesian acceptable for interethnic communication among educated native speakers and commonly used in the media. Students engage in task-based activities set in real-life situations as they speak and write in Indonesian, thus acquiring grammatical accuracy while immersing themselves in the cultural context. Each lesson revolves around a grammatical construction presented in a conversation, narrative, or letter. Online recordings are available, allowing students to reinforce the learning of the grammatical forms. Lessons first offer the student the opportunity to see and hear the grammar in use, then to practice the grammatical form, and finally to read an explanation of the grammatical rule in English. Numerous illustrations and photographs aid in learning the language and culture without excessive use of translation. In addition, cultural notes at the end of each lesson allow students to explore the relationship between language use and socio-cultural values and customs.